Public Morality as a Fulcrum for Social Cohesion and Development in Nigeria: A Philosophical Approach - Adegboyega, Oyekunle Oluwayemisi (NIU Journal of Humanities, 2020)
This paper adopts the analytical method of philosophy to evaluate the state of public morality in Nigeria. It espouse the idea that the neglect of public morality in any society is diametrically opposed to her development and growth. Such society experiences injustice, instability, public corruption, social-disorder and many other vices that are inimical to the existence of a political society. The contemporary Nigerian society is not faring differently from these negative indices. The Nigerian society is characterized by various economic depression, political instability, and constitutional crises. These crises have eroded the joy of independence, as the reality of the situation in the society shows hunger and deprivation. The negative socio-economic, political, and health impacts of these crises on the citizens have made many people to conclude that Nigeria is a failed state. While this paper identified the breakdown of public morality as the cause of these crises, it also attempts a solution on how public morality can be restored in Nigeria in order that stability, social order, good life for the citizens, growth and development may be attained.                Keywords: Public Morality, Politics, Nigerian Society, Social Order and Development.